Development of a Social Accountability Model in Papua New Guinea Border Villages - Falah, Syaikhul; Patma, Kurniawan (Universitas Cenderawasih, 2024)
This research examined social accountability in village fund management in the Papua New Guinea border region, specifically in the villages of Skow Sae, Skow Mabo, and Moso. The study aimed to assess how information transparency and service monitoring impact community participation. Data were collected through in-depth interviews, document studies, and questionnaires, with 69 out of 150 questionnaires returned. The analysis uses the TETRAD tool to generate a questionnaire model that is then administered to respondents. This research sample employs a purposive method, specifically targeting respondents who possess knowledge and actively participate in the management of village funds. The findings revealed that effective service monitoring positively influences community participation, whereas information transparency does not always lead to increased participation. The research underscores the importance of collaborative efforts between village governments and communities to enhance social accountability and ensure fair resource distribution. Despite the model's limitations due to the small sample size, the study highlights the need for improved facilities, training, and digital platforms to support transparency and accountability in village governance